Assistance in Senen Goat Milk Management as an Effort to Improve The Community's Economy Through The Asset-Basset Community Development (ABCD) Approach - Ahmad Khumaidi; Kustiana Arisanti (Simfoni Ilmu Cindekia, 2024)
The application of the Asset-Basset Community Developent (ABCD) method was carried out at the UNZAH Real Work Lecture (KKN) in Pesawahan Village. The assisted subject in the program is Mrs. Erni as the owner of a goat's milk business in Sumanbito Hamlet, Pesawahan Village. The reason we chose the subject of goat's milk business assistance is because this business activity is a business that is rarely owned by other villages. In addition, goat's milk business has a high selling value with various health benefits. The purpose of the assistance is to educate goat milk business managers regarding product innovation and marketing techniques through social media/market places so that business productivity can increase.